Nanosecond X-ray photon correlation spectroscopy using pulse time structure of a storage-ring source. (2021) - Jo, Wonhyuk; Westermeier, Fabian; Rysov, Rustam; Leupold, Olaf; Schulz, Florian; Tober, Steffen; Markmann, Verena; Sprung, Michael; Ricci, Allesandro; Laurus, Torsten; Aschkan, Allahgholi; Klyuev, a Alexander; et al.
No abstract available